DETERMINAN BELANJA MODAL PADA PEMERINTAH PROVINSI DI SUMATERA - Madry, Madry; Maria, Maria; Nurhasanah, Nurhasanah (ISAS, 2025)
This research aims to determine the effect of Regional Original Income (PAD), Special Allocation Fund (DAK), regional wealth, and tax effort on capital expenditure in provincial governments in Sumatra. In this research, researchers use quantitative research types, with document data collection techniques sourced from secondary data obtained from the Audit Result Report (LHP) LKPD BPK RI. This research uses a saturated sampling method with a population of 10 Provincial Governments in Sumatra for 5 years from 2018 to 2022, with 50 observation units. Data analysis techniques and multiple linear regression assisted by SPSS version 26. The results of the analysis show that both partially and simultaneously PAD, DAK, regional wealth and tax effort have a positive and significant effect on capital expenditure by 61.9%. Keywords: Regional Original Income, Special Allocation Funds, Regional Wealth, Tax Effort, Capital Expenditures